Identification and molecular characterisation of Taro bacilliform virus and Taro bacilliform CH virus from East Africa - Kidanemariam, Dawit B.; Sukal, A.C.; Abraham, Adane D.; Stomeo, Francesca; Dale, J.L.; James, A.P.; Harding, R.M. (Wiley, 2018)
Taro (Colocasia esculenta) and tannia (Xanthosoma sp.) are important root crops cultivated mainly by small‐scale farmers in sub‐Saharan Africa and the South Pacific. Viruses are known to be one of the most important constraints to production, with infections resulting in severe yield reduction. In 2014 and 2015, surveys were conducted in Ethiopia, Kenya, Tanzania and Uganda to determine the identity of viruses infecting taro in East Africa. Screening of 392 samples collected from the region using degenerate badnavirus primers revealed an incidence of 58–74% among the four countries surveyed, with sequence analysis identifying both Taro bacilliform virus (TaBV) and Taro bacilliform CH virus (TaBCHV). TaBCHV was identified from all four countries while TaBV was identified in all except Ethiopia. Full‐length sequences from representative TaBV and TaBCHV isolates showed that the genome organization of TaBV isolates from East Africa was consistent with previous reports while TaBCHV isolates from East Africa were found to encode only four ORFs, distinct from a previous report from China. Phylogenetic analysis showed that all East African TaBV isolates form a single subgroup within known TaBV isolates, while TaBCHV isolates form at least two distinct subgroups. To the authors' knowledge, this is the first report describing the occurrence and genome organization of TaBV and TaBCHV isolates from East Africa and the first full‐length sequence of the two viruses from tannia.